The effects of grinding aids on modelling of air classification of cement. (30th January 2018) - Toprak, Nurettin Alper; Altun, Okay; Benzer, Ahmet Hakan
Highlights: This study investigated the effects of grinding aids on air classification performance. Dosage rate and the type of grinding aids had effects on air classification performance. Grinding aid based classification model was developed. Abstract: Until so far, several studies have been performed on grinding aids which have discussed the influences. However, the evaluations were all based on closed circuited grinding operations where the milling and the classification operations were integrated and had effect with each other. The novelty of this paper comes from its comprehensive test works with only on air classifier and development of grinding aid-specific model structure that has not been performed. Within the scope, laboratory scale air classifier was utilized and triethanolamine (TEA), triisopropanolamine (TIPA), and diethylenglycol (DEG) were mixed with cement at various dosage rates. The experimental tests were performed at different wheel speed and air flow rates then the performance of the air classification was evaluated by plotting the Tromp curves. As a result, the limited change was observed for cut size and sharpness parameters however, bypass and fish hook parameters changed significantly. Among the grinding aids tested, TIPA type aid was found to be more effective on both bypass and fish hook parameters. Finally, the air classifier was modelled by using Whiten's equation and the relations between dosage rate, type and model parameters were investigated. The results concluded that different types of grinding aids had varied influences and the model structures needed to be developed accordingly.